Putting objects in context: A prefrontal–hippocampal–perirhinal cortex network - Barker, G. R. I. (Brain Neurosci Adv, 2020)
When we encounter an object, we spontaneously form associations between the object and the environment in which it was encountered. These associations can take a number of different forms, which include location and context. A neural circuit between the hippocampus, medial prefrontal cortex and perirhinal cortex is critical for object-location and object-sequence associations; however, how this neural circuit contributes to the formation of object-context associations has not been established. Bilateral lesions were made in the hippocampus, medial prefrontal cortex or perirhinal cortex to examine each region contribution to object-context memory formation. Next, a disconnection lesion approach was used to examine the necessity of functional interactions between the hippocampus and medial prefrontal cortex or perirhinal cortex. Spontaneous tests of preferential exploration were used to assess memory for different types of object-context associations. Bilateral lesion in the hippocampus, medial prefrontal cortex or perirhinal cortex impaired performance in both an object-place-context and an object-context task. Disconnection of the hippocampus from either the medial prefrontal cortex or perirhinal cortex impaired performance in both the object-place-context and object-context task. Interestingly, when object recognition memory was tested with a context switch between encoding and test, performance in the hippocampal and medial prefrontal cortex lesion groups was disrupted and performance in each disconnection group (i.e. hippocampus + medial prefrontal cortex, hippocampus + perirhinal cortex) was significantly impaired. Overall, these experiments establish the importance of the hippocampal-medial prefrontal-perirhinal cortex circuit for the formation of object-context associations.